Effect of micro blasting process parameters on 3D surface topography and surface properties of zirconia (Y‐TZP) ceramics - Okan Yetik; Berzah Yavuzyegit; Yasemin Yıldıran Avcu; Hürol Koçoğlu; Gürel Pekkan; Serkan Sarıdağ; Mert Guney; Egemen Avcu (Engineering Reports, 2021)
Abstract The present study aims to examine the effects of operational parameters on the surface topography and wear mechanisms of monolithic and conventional yttria‐stabilized zirconia (Y‐TZP) ceramics in the micro blasting process, performed under various acceleration pressures (1.5–3 bar), particle impact angles (30°–90°), and erodent particle sizes (50–460 μm). Three‐dimensional (3D) surface topography, surface roughness, and surface morphology of micro‐blasted specimens were analyzed by using non‐contact optical profilometry and SEM‐EDS. The micro blasting characteristics of both Y‐TZP were similar that increased blasting pressure and erodent particle size increased surface roughness. Erosion rate increased with increasing blasting pressure, whereas it decreased with increasing erodent particle size. Particle size was the most effective parameter on changing surface topography, while the particle impact angle had no distinct effect on the erosion rate, surface roughness, and surface topography of Y‐TZP ceramics. SEM‐EDS analyses showed that the primary wear mechanism during micro blasting was micro‐cutting with a substantial amount of embedded particles on the material's surface.